Knowledge in Distance Learning System - Nycz, Małgorzata; Smok, Barbara (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Knowledge management is still growing in importance, also in the field of computer supported education systems. This paper presents models of education, characteristic of distance education system. Special stress has been put to knowledge treated as one of the most valuable assets. Then we discuss organization of distance education system and at the end we give some hints about the future of distance learning systems.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 105-112